IL1 gene polymorphisms in relation to external apical root resorption concurrent with orthodontia - Linhartova, P; Cernochova, P; Izakovicova Holla, L (Oral diseases, 2013)
Objective External apical root resorption (EARR) is permanent shortening of the end of the tooth root. It is a common clinical complication of orthodontic treatment. Polymorphisms in the interleukin 1 (IL1) gene cluster have been related to an increased EARR risk. The aim of this study was to analyze possible associations of IL1 gene variants with EARR in Czech population. Subjects and Methods In this case–control study, 32 patients with EARR (age 15.0 ± 4.1 years) and 74 controls (age 15.2 ± 5.3 years) were genotyped using PCR‐based methods for IL1A (−889C/T), IL1B (+3953C/T), and IL1RN [IL1 receptor antagonist, variable number tandem repeat (VNTR)] gene polymorphisms. Results While no statistical significant differences in the IL1A and IL1B genotype, allele and reconstructed IL1 haplotype frequencies between patients with EARR and controls were found, marginally significant differences were observed in the frequencies of IL1RN variant (P = 0.05 for *22 genotype and P = 0.06 for a short (2) allele). In addition, significant associations between IL1RN*12, *22 genotypes and the short (2) allele and EARR were identified in the subgroup of girls (P = 0.04 and P = 0.02, P = 0.02). Conclusions Although no significant role of IL1A (−889C/T) and IL1B (+3953C/T) variants in EARR was confirmed, IL1RN VNTR may be associated with EARR, especially in girls.